A Cost Minimization Analysis of Treatment Options for Postmenopausal Women With Dysuria. Issue 8 (August 2019) - Bradley, Megan S.; Beigi, Richard H.; Shepherd, Jonathan P.
Abstract : (Abstracted from Am J Obstet Gynecol 2019; doi: 10.1016/j.ajog.2019.04.031) The most common type of bacterial infection seen in an outpatient setting is urinary tract infection (UTI). In the United States, the overall lifetime prevalence of UTIs in women is greater than 50%.